Survival factors of brazilian family businesses crossing the third generation of succession (Research, Society and Development, 2023)
Family businesses represent 90% of Brazilian companies and play a significant role in the national and global economy. They emerged alongside the establishment of Brazil during the colonial period and were among the country's earliest institutions. Despite their significance, family businesses tend to have a short lifespan. Statistics indicate that only 30% of family businesses survive into the second generation of succession, and only 5% make it to the third generation. These figures reveal an emerging challenge for the Brazilian economy's health, underscoring the importance of identifying the factors involved in succession and potential causes of long-term failure. Therefore, this literature review aimed to understand, through studies on the subject, the importance of family businesses in the Brazilian context and the primary causes of bankruptcy. It also sought to explore the role of organizational and work psychology in the succession process and as a survival factor for these businesses. Additionally, the study aimed to find strategies that could contribute to the longevity of these organizations. From the analyzed studies, it became evident that the primary conflicts affecting family businesses are relational in nature, linked to the lack of professionalism and resistance to modernization. These conflicts often arise from the difficulty in setting boundaries in the relationships between the family and the business, as family behavioral patterns extend beyond personal boundaries, becoming dysfunctional in the business context.